Kerjasama Sekolah Dan Keluarga Dalam Pendidikan Karakter Dengan Pola Mindset Pengembangan Diri - Raihanah Raihanah (Pusat Riset dan Inovasi Nasional, 2022)
Public schools in Indonesia are still tormented by various problems. One of them is the moral decline among students. Achievements in training, especially learning provided by educators to students, are not only related to the right techniques and strategies, but also related to school and family participation in character learning by directing the students' own mentality. Family participation with teaching units is very important, school units are obliged to support family collaboration and inclusion in encouraging their children's schooling. In this joint effort, of course, the development of one's mentality from an early age by families and schools on the grounds that the perspective or approach of student attitudes that are correct from the start will affect the overall existence of students in the future. This research uses a qualitative approach with the type of case study research. The research was conducted at MIN 27 HSU Jingah Bujur Village, Kec. Haur Ivory. Based on the results of different examinations, it shows that participation between families and schools and instilling a mindset from an early age affect the improvement of progress in character education and the achievements of their children.